2015
DOI: 10.1080/13102818.2015.1057525
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between physical function, disease activity, spinal mobility and bone parameters (trabecular bone score and bone mineral density) in ankylosing spondylitis patients

Abstract: (2015) Relationship between physical function, disease activity, spinal mobility and bone parameters (trabecular bone score and bone mineral density) in ankylosing spondylitis patients, Biotechnology & Biotechnological Equipment, 29:5, 956-962, DOI: 10.1080/13102818.2015 This study aimed to evaluate the relationship between physical function, disease activity, spinal mobility and bone parameters in ankylosing spondylitis (AS) patients. Fifty patients (27 men and 23 women) were examined. The clinical assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Moreover, more evident alterations are also reported in bone microarchitecture in older patients, without significant differences between genders. There was an inverse correlation between the mobility scores and the three bone parameters (TBS, BMD, and T-score femoral), showing a relationship between the state of skeletal health and vertebral functional deterioration (50).…”
Section: Tbs and Ankylosing Spondylitismentioning
confidence: 86%
See 4 more Smart Citations
“…Moreover, more evident alterations are also reported in bone microarchitecture in older patients, without significant differences between genders. There was an inverse correlation between the mobility scores and the three bone parameters (TBS, BMD, and T-score femoral), showing a relationship between the state of skeletal health and vertebral functional deterioration (50).…”
Section: Tbs and Ankylosing Spondylitismentioning
confidence: 86%
“…The lumbar spine BMD did not differ between AS and HS patients, whilst there was a decrease in the hip T-score in AS patients (p = 0.02) (44). Several studies reported a 25% OP prevalence in AS patients and from 10 to 43% radiographic vertebral fractures (17,18,(47)(48)(49)(50)(51).…”
Section: Tbs and Ankylosing Spondylitismentioning
confidence: 89%
See 3 more Smart Citations